M. Cherif Bassiouni (1937–2017) - Sadat, Leila Nadya (Proceedings of the ASIL Annual Meeting, 2018)
From the torture convention to the Statute of the International Criminal Court, his fingerprints are on every major international criminal law instrument of the past fifty years, including the emerging new convention on crimes against humanity. Some of his very first writings as a young academic concerned the question of Palestine, including an essay on “The Middle East in Transition: From War to War, a Proposed Solution,” an astonishingly brave writing for a young academic at a U.S. university.5 Yet he was never bitter or angry, understanding that peace between different religious communities could result only from tolerance and education. 3 Model Draft Statute for the International Criminal Court Based on the Preparatory Committee's Text to the Diplomatic Conference, Rome, June 15–July 17, 1998, 13 ter Nouvelles Etudes Pénales (Leila Sadat & M. Cherif Bassiouni eds., 1998).